The Occupational Structures of Low- and High-Wage Service Sector Establishments. Issue 2 (May 2019) - Forsythe, Eliza C.
The occupational structure of an establishment provides a description of its production process by detailing the distribution and relative intensity of tasks performed. In this study, the author investigates whether there are substantive differences in the occupational structures of low- and high-wage service sector establishments. The author shows that low-wage establishments organize production to use less labor in professional occupations compared with high-wage establishments operating in the same local labor market and industry. In addition, low-wage establishments employ fewer individuals in information technology occupations, employ fewer managers, and have substantially wider supervisory spans of control. These results indicate that, despite operating in the same narrowly defined labor and product markets, low-wage establishments organize production to less intensively use labor in skilled occupations.